2022
DOI: 10.1155/2022/3891109
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Bodybuilding and Fitness Exercise on Physical Fitness Based on Deep Learning

Abstract: With the rapid development of society and economy, people’s living standards are improving day by day, and increasingly attention is paid to physical health, which has set off a fitness upsurge. The purpose of this paper was to analyze the impact of bodybuilding exercise on physical fitness based on deep learning. It provides a reference for fitness enthusiasts to choose scientific and targeted exercise methods, and provides a theoretical basis for the promotion of bodybuilding and fitness. This paper first gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…As an example, the study in [16] analyzed the importance of physical fitness in case of adolescent individuals and based on the results proposed to improve the physical fitness training for service system. The study in [17,18] used image segmentation on deep learning models to design experiments emphasizing on body building and fitness. The recurrent neural network and gated recurrent neural network were used to compare, analyze, and determine the stability of data processing when subjected to different activation functions.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the study in [16] analyzed the importance of physical fitness in case of adolescent individuals and based on the results proposed to improve the physical fitness training for service system. The study in [17,18] used image segmentation on deep learning models to design experiments emphasizing on body building and fitness. The recurrent neural network and gated recurrent neural network were used to compare, analyze, and determine the stability of data processing when subjected to different activation functions.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has focused on psychological training in competitive sport [61,62], but studies on how the athletes' perceptions of the dynamics of personality and implicit autonomy undergo changes in relation to the sporting age category and the athletic experience are relatively few and do not address competitive bodybuilders [63][64][65]. Identifying the perception differences regarding the characteristics of personality and autonomy according to the sports age category, we consider that it will facilitate the expansion of knowledge, highlighting the importance of sports psychology in improving the training process of competitive bodybuilders.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%